The Relationship between Lecturer Leadership, Academic Service Quality, and Administrative Service Quality with Student Satisfaction at STIKes Buleleng Bali - Sundayana I Made; Sulis Diana; Dhonna Anggreni (Universitas STRADA Indonesia, 2025)
Background: The low quality of graduates will have an impact on various problems such as graduates not being able to continue their education to a higher level, not being accepted into the world of work or being accepted to work but not excelling, and graduates are not productive. Purpose: To determine the relationship between lecturer leadership, academic service quality, and administrative service quality with student satisfaction at STIKES Buleleng Bali. Methods: The type of observational analytical research with cross sectional. independent variables: lecturer leadership, quality of academic services, and quality of administrative services, dependent variables: student satisfaction. the population of all STIKES Buleleng students, random sampling cluster of 241 people. Questionnaire data collection techniques, spearman correlation test and multivariate test: logistic regression. Results: The results of the statistical test showed a relationship between lecturer leadership and student satisfaction which showed a figure of 0.000 (p<0.005), there was a relationship between academic services and student satisfaction of 0.00 (p<0.05) there was a significant relationship between administrative services and student satisfaction, which was 0.00 (p<0.05). In the multivariate test, there was a strong relationship between lecturer leadership variables and academic services with student satisfaction, while administrative services did not. Conclusion: Lecturer leadership and academic services with satisfaction, while administrative services have no effect, suggesting the need for the concept of Total Quality Management (TQM) for STIKES Buleleng, especially administrative services.